First International Conference on Optical Communications and Networks (ICOCN 2002) Shangri-La Hotel, Singapore, 11-14 November 2002 - International Conference on Optical Communications and Networks 2002 : Singapore); Omidyar, Cambyse Guy, 1944-; Ghafouri-Shiraz, H.; Zhong, W. D. (Wen De) (New Jersey ; Singapore : World Scientific, 2002)
The proceedings of the First International Conference on Optical Communications and Networks present high quality recent research results in the areas of optical communications, network components, architectures, protocols, planning, design, management and operation.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Optical communications -- Congresses; Fiber optics -- Congresses; Computer networks -- Congresses; Optoelectronics -- Congresses; TECHNOLOGY & ENGINEERING / Imaging Systems; Electronic books